2023
DOI: 10.1093/jxb/erad215
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of ammonium nutrition with essential mineral cations

Abstract: Plant growth and development depends on sufficient nutrient availability in soils. Agricultural soils are generally nitrogen (N) deficient and thus, soils need to be supplemented with fertilizers. Ammonium (NH4  +) is a major inorganic N source. However, at high concentrations ammonium nutrition becomes a stress situation that inhibits plant growth. The cause of ammonium stress or toxicity is multi-factorial but the interaction with other nutrients is among the main determinants of plants sensitivity towards h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 131 publications
0
1
0
Order By: Relevance
“…The two experiments carried out in this study showed that DMPP stabilized-NH 4 + decreased the overall plant shoot biomass by 10% in unlimed soil (Figures 2 and 5). The negative effect of sole NH 4 + -N nutrition in plants is welldocumented in the literature and is ascribed to several factors directly or indirectly linked to NH 4 + -N uptake, accumulation, and assimilation (Britto & Kronzucker, 2002;Coleto et al, 2023;Kong et al, 2022). For instance, such factors include acidification of the rhizosphere beyond critical levels for plant growth, increased strength of the root tissue as a carbon sink under NH 4 + -N nutrition due to enhanced synthesis of amino acids, and the adverse effect on the uptake of the other cationic nutrients (Kong et al, 2022).…”
Section: + Induces Reduced Plant Growth In Unlimed Acidic Sandy Soilmentioning
confidence: 99%
“…The two experiments carried out in this study showed that DMPP stabilized-NH 4 + decreased the overall plant shoot biomass by 10% in unlimed soil (Figures 2 and 5). The negative effect of sole NH 4 + -N nutrition in plants is welldocumented in the literature and is ascribed to several factors directly or indirectly linked to NH 4 + -N uptake, accumulation, and assimilation (Britto & Kronzucker, 2002;Coleto et al, 2023;Kong et al, 2022). For instance, such factors include acidification of the rhizosphere beyond critical levels for plant growth, increased strength of the root tissue as a carbon sink under NH 4 + -N nutrition due to enhanced synthesis of amino acids, and the adverse effect on the uptake of the other cationic nutrients (Kong et al, 2022).…”
Section: + Induces Reduced Plant Growth In Unlimed Acidic Sandy Soilmentioning
confidence: 99%